Global Uncertainty and the Volatility of Agricultural Commodities Prices - Munier, Bertrand R (IOS Press, 2014)
Commodities markets and prices have become a sort of Babel Tower of topics since the turn of the century. They once were a specific part of energy economics for oil and coal, of natural resources economics for minerals and precious metals, of agricultural economics regarding wheat, corn, rice, fruits and vegetables, and more generally regarding food grown on land. This traditional view of the markets for commodities appears today as jeopardized. This book wants to explore to what extent it has to be questioned regarding agricultural commodities. Main institutional changes occurred at the end of the Nineties, with two major acts passed under the second term of the Clinton Presidency